2022
DOI: 10.1155/2022/3155845
|View full text |Cite
|
Sign up to set email alerts
|

Global Status of Emerging Lophomonas Infection: A Systematic Review of Reported Cases (1993—2020)

Abstract: Purpose. Lophomonas spp., is an emerging protozoan parasite that belongs to the Parabasalids (Parabasalia, lophomonadida) which infects the respiratory tracts of humans. Despite the presence of a few reports of human lophomoniasis, the true burden of Lophomonas infection is unknown. This systematic review aimed to elucidate the latest global status of publications reporting human cases of lophomoniasis as a new emerging protozoal disease. Methods. A comprehensive and systematic search was performed in 10 (five… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 38 publications
0
13
0
Order By: Relevance
“…However, owing to the similarity of symptoms with other respiratory conditions, diagnosis based solely on clinical findings can be challenging. 1 The main countries reporting cases of L. blattarum infection include China, Iran, and India. 1 In our case, the diagnosis of L. blattarum was established through bronchoscopy and subsequent analysis of BALF at the INRCL.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, owing to the similarity of symptoms with other respiratory conditions, diagnosis based solely on clinical findings can be challenging. 1 The main countries reporting cases of L. blattarum infection include China, Iran, and India. 1 In our case, the diagnosis of L. blattarum was established through bronchoscopy and subsequent analysis of BALF at the INRCL.…”
Section: Discussionmentioning
confidence: 99%
“…1 The main countries reporting cases of L. blattarum infection include China, Iran, and India. 1 In our case, the diagnosis of L. blattarum was established through bronchoscopy and subsequent analysis of BALF at the INRCL. Identification of the mobile flagellated protozoan under light microscopy confirmed the presence of L. blattarum.…”
Section: Discussionmentioning
confidence: 99%
“…Pulmonary lophomoniasis majorly affects Latin American and Asian countries, such as Panama and Iran, with a prevalence of 35% and 22.7%, respectively, specifically among people aged >60 years [ 2 , 3 ]. The transmission of Lophomonas to humans remains unclear, albeit certain environmental situations such as rain, temperature, humidity, and geographic latitude have been considered to facilitate the development of the transmitter ( L. blattarum ) [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…For the development of this disease, immunosuppression or underlying diseases such as tuberculosis (TB) or COPD were considered contributing factors [ 7–9 ]. However, up to 68% of these patients have been reported to be immunocompetents [ 2 , 10 ], possibly due to the temperature and humidity of the bronchial tree, which allows favorable conditions that allow the release of the cyst and adhering firmly to the respiratory mucosa to cause cell damage via cytoadherence, protease, rupture of epithelial barriers, and induction to apoptosis [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Data from a systematic review showed that lophomoniasis cases were reported from 10 countries, mostly from Asian countries, such as Iran and China. However, the global true burden of the disease is still unknown [ 6 ]. The main symptoms of BPL are cough, low-grade fever, and dyspnea.…”
Section: Introductionmentioning
confidence: 99%